Changes in public perceptions and experiences of the Australian health‐care system: A decade of change. (20th November 2020) - Ellis, Louise A.; Pomare, Chiara; Gillespie, James A.; Root, Jo; Ansell, James; Holt, Joanna; Wells, Leanne; Tran, Yvonne; Braithwaite, Jeffrey; Zurynski, Yvonne
Abstract: Background: The views and experiences of the Australian public are an important barometer of the health system. This study provides key findings about the changing views held by Australians over time regarding their individual experiences and perceptions of the overall performance of the health system. Methods: A population‐based online survey was conducted in 2018 (N = 1024). Participants were recruited through market research panels. The results were compared with previous Australian population survey data sets from 2008 (N = 1146), 2010 (N = 1201) and 2012 (N = 1200), each of which used different population samples. The survey included questions consistent with previous surveys regarding self‐reported health status, and questions about use, opinions and experiences of the health system. Results: Overall, there has been a shift in views from 2008 to 2018, with a higher proportion of respondents now viewing the Australian health‐care system more positively ( X 2 (2, N = 4543) = 96.59, P  < .001). In 2018, areas for attention continued to include the following: the need for more doctors, nurses and other health workers (29.0%); lower costs for care or Orion medicines (27.8%); more access to care (13.1%); and enhancements in residential aged care (17.3% rated these services as 'bad' or 'very bad'). Conclusions: This research suggests that Australians' perceptions of their health‐care system have significantly improved over the last decade; however, concerns have emerged over access to medicines, inadequate workforce capacity and the quality of aged care facilities. Our study highlights the value of periodically conducting public sentiment surveys to identify potential emerging health system problems.